Surface roughness and surface hardness changes in composite resin provisional crown before and after brushing with whitening toothpaste - Dea S. Putri; Ika Andryas (Journal of Dentomaxillofacial Science, 2022)
Objective: To determine the surface roughness and surface hardness difference in composite resin provisional crown before and after brushing with whitening toothpaste. Material and Methods: This was a pre- and post-test group design experimental study. In this study, the sample was a composite resin provisional crown based on bis-acryl. The number of samples in this study was 32 samples, 16 for the surface roughness test and the other 16 for the surface hardness test. Each sample was brushed using a V8-Brushing Machine Modified, then tested for surface roughness and hardness using a Profilometer and Vickers Hardness Tester. Result: The paired T test was used to analyze the results statistically. There was a significant difference between the groups before and after brushing with whitening toothpaste. (p<0.05). Conclusion: After simulated brushing with whitening toothpaste, there was a change in the the provisional crown material surface roughness and hardness value.